CD371-positive pediatric B-cell acute lymphoblastic leukemia: propensity to lineage switch and slow early response to treatment - Buldini, Barbara; Varotto, Elena; Maurer-Granofszky, Margarita; Gaipa, Giuseppe; Schumich, Angela; Brüggemann, Monika; Mejstrikova, Ester; Cazzaniga, Giovanni; Hrusak, Ondrej; Szczepanowski, Monika; Scarparo, Pamela; Zimmermann, Martin; et al. (Blood, 2024)
In the effort to improve immunophenotyping and minimal residual disease (MRD) assessment in acute lymphoblastic leukemia (ALL), the international Berlin-Frankfurt-Münster (iBFM) Flow Network introduced the myelomonocytic marker CD371 for a large prospective characterization with a long follow-up. In the present study, we aimed to investigate the clinical and biological features of CD371-positive (CD371pos) pediatric B-cell precursor ALL (BCP-ALL). From June 2014 to February 2017, 1812 pediatric patients with newly diagnosed BCP-ALLs enrolled in trial AIEOP-BFM ALL 2009 were evaluated as part of either a screening (n = 843, Italian centers) or validation cohort (n = 969, other iBFM centers). Laboratory assessment at diagnosis consisted of morphological, immunophenotypic, and genetic analysis. Response assessment relied on morphology, multiparametric flow cytometry (MFC), and polymerase chain reaction (PCR)-MRD. At diagnosis, 160 of 1812 (8.8%) BCP-ALLs were CD371pos. This correlated with older age, lower ETV6::RUNX1 frequency, immunophenotypic immaturity (all P < .001), and strong expression of CD34 and of CD45 (P < .05). During induction therapy, CD371pos BCP-ALLs showed a transient myelomonocytic switch (mm-SW: up to 65.4% of samples at day 15) and an inferior response to chemotherapy (slow early response, P < .001). However, the 5-year event-free survival was 88.3%. Among 420 patients from the validation cohort, 27 of 28 (96.4%) cases positive for DUX4-fusions were CD371pos. In conclusion, in the largest pediatric cohort, CD371 is the most sensitive marker of transient mm-SW, whose recognition is essential for proper MFC MRD assessment. CD371pos is associated to poor early treatment response, although a good outcome can be reached after MRD-based ALL-related therapies.
Keywords: reziduální nádor; Immunophenotyping; pre-B-buněčná leukemie; imunofenotypizace; kojenec; mladiství; Neoplasm, Residual; mužské pohlaví; tetraspaniny; Infant; dítě; Cell Lineage; Child; Child, Preschool; buněčný rodokmen; ženské pohlaví; Humans; předškolní dítě; Tetraspanins; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; Female; Adolescent; lidé; Male